The features of experimental allergic encephalomyelitis after stem cells transplantation - Pichkur, Leonid D.; Semenova, Vira M.; Verbovska, Svitlana A.; Oleksenko, Natalia P.; Akinola, Samuel T. (Ukrainian Neurosurgical Journal, 2017)
The objective. To study the course of experimental allergic encephalomyelitis (EAE) after intravenous administration of hematopoietic stem cells (HSC) and suboccipital transplantation of fetal neurocells (FNC), and treatment impact on intensity of neural tissue renewing in rats with EAE. Materials and methods. The experiment included 40 rats, average weight 200 g. EAE was induced using complete Freund’s adjuvant. In 32 rats with EAE we used intravenous HSK (10 million cells or 20 million cells) and suboccipital transplantation of FNC (0.1 ml). The EAE clinical course was estimated up to 110 days. The rats were taken from the experiment on 23rd, 25th days and in 2 months after EAE induction. The preparations were stained by Nisse, with hematoxylin, eosin and picro-fuchsin. Morphological and morphometric studies were performed. Results. Complete recovery was not observed, and on the 26th day of the experiment EAE was regarded as a chronic process. After allogeneic HSC administration (in dose 10 million cells) peak of clinical manifestations was observed on the 20th day of the experiment with animals’ gradual complete recovery. Administration of allogeneic HSC in a dose of 20 million cells leads to significantly more rapid regression of clinical signs compared to the treatment with allogeneic HSC in a dose of 10 million cells. Animals’ recovery after intravenous introduction of HSC and suboccipital transplantation of FNC was significantly more rapid than after treatment just with HSC. The treatment with intravenous introduction of HSC (20 million cells) and suboccipital transplantation of FNC was associated with temporary significant deterioration after HSC administration and rapid recovery after FNC application (on the 29th day). In all treatment options we revealed the tendency to reduction of pathologically changed neurocyts and gliocyts number. Conclusion. Suboccipital administration of allogeneic FNC improves the clinical condition of rats with EAE. The best results of experimental EAE treatment were observed at intravenous administration of HSC (20 million cells) followed by FNC neurotransplantation, particularly on the 63rd day.